Revestimento superhidrofóbico com celulose bacteriana funcionalizada para aplicação em embalagens de alimentos - Frota, Maryana Melo (2023)
Superhydrophobic (SH) surfaces are known to have high contact angle (CA) and low sliding angle (SA) values. They are considered technological innovations for the packaging sector to combat food waste and reduce accumulation of organic waste inside food containers. The use of organic matrices from renewable sources, such as food waxes, combined with nanometric structures, such as functionalized bacterial cellulose (BCn), can improve the stability and durability of superhydrophobic surfaces. The applicability of BC can be expanded through functionalization reactions in its matrix, allowing the insertion of nonpolar molecules that enhance its hydrophobicity. Therefore, the objective of the present study was to develop a coating with beeswax (BW) and functionalized bacterial cellulose nanofibrils, added as a structuring matrix, to obtain superhydrophobic properties with potential applicability for food packaging. BC was synthesized through static fermentation with Camellia sinensis, sucrose and the symbiotic consortium of bacteria and yeast (SCOBY), then purified, neutralized, and defibrillated in a colloidal mill. The functionalization process started from a study at different pHs (3.5 to 7.5) for process optimization purposes. By comparing the intensities of the bands obtained after the functionalization process at different pHs, it was possible to determine the most suitable medium for bonds between bacterial cellulose and silicon dioxide. After that, the functionalized material (BCn) was characterized in terms of morphology and thermal profile. For the development of superhydrophobic coatings, a complete factorial design was applied (2 2 ) with the independent variables being the concentrations of BW and BCn and the dependent variables being the CA and SA analyses. Three coatings were then created: BWcontrol (only with beeswax); BW/BCn (beeswax and BCn without modification); and BW/BCn-SiO 2 (beeswax and BCn functionalized with SiO 2 ), followed by characterization regarding chemical composition, morphology, wettability profile, optical properties, durability tests, toxicological profile and superhydrophobic properties (repellent to liquid foods and self-cleaning capacity). The IR spectra of BCn at pH 4.5 showed better interaction of cellulose with silanol groups through the evaluation of band intensity for functionalization purposes. As a result, SiO 2 was responsible for modifying the BCn surface and making the material more thermally stable. Furthermore, the BW/BCn-SiO 2 coating, with a micro and nanoscale surface, presented a CA of 153° and a SA of 3°, proving the achievement of superhydrophobic surfaces. The coating applied to glass slides showed excellent adhesion to surface, mechanical resistance, and storage stability at low temperatures. For purposes of applicability in contact with food, toxicological tests with Artemia salina nauplii confirmed the non-toxicity of the coating materials. In tests with food, the SH coating was able to repel liquid and viscous foods, in addition to having self-cleaning capabilities. Therefore, the results obtained in this work show how promising and innovative the method of functionalizing cellulosic materials of bacterial origin using food-based silicon-based compounds is, showing high potential for applicability on packaging surfaces with superhydrophobic and repellent characteristics, with the aim of reducing the adhesion of organic residues inside food packaging.